Vascular growth responses to chronic arterial occlusion are unaffected by myeloid specific focal adhesion kinase (FAK) deletion - Heuslein, Joshua L. (Sci Rep, 2016)
Arteriogenesis, or the lumenal expansion of pre-existing arterioles in the presence of an upstream occlusion, is a fundamental vascular growth response. Though alterations in shear stress stimulate arteriogenesis, the migration of monocytes into the perivascular space surrounding collateral arteries and their differentiation into macrophages is critical for this vascular growth response to occur. Focal adhesion kinase’s (FAK) role in regulating cell migration has recently been expanded to primary macrophages. We therefore investigated the effect of the myeloid-specific conditional deletion of FAK on vascular remodeling in the mouse femoral arterial ligation (FAL) model. Using laser Doppler perfusion imaging, whole mount imaging of vascular casted gracilis muscles, and immunostaining for CD31 in gastrocnemius muscles cross-sections, we found that there were no statistical differences in perfusion recovery, arteriogenesis, or angiogenesis 28 days after FAL. We therefore sought to determine FAK expression in different myeloid cell populations. We found that FAK is expressed at equally low levels in Ly6C(hi) and Ly6C(lo) blood monocytes, however expression is increased over 2-fold in bone marrow derived macrophages. Ultimately, these results suggest that FAK is not required for monocyte migration to the perivascular space and that vascular remodeling following arterial occlusion occurs independently of myeloid specific FAK.